The Reality of the Commitment of Algerian Economic Institutions to the Application of Deferred Taxes: A Field Study of the Opinions of a Sample of Specialists in Accounting and Taxes - Djonit, Adel (المركز الجامعي مرسلي عبدالله بتيبازة, 2023)
تهدف هذه الدراسة إلى قياس درجة الالتزام بالضرائب المؤجلة في الجزائر، ودراسة وتحليل مستوى الالتزام بالضريبة المؤجلة من خلال استبيان وزع على (97) محاسب وخبير محاسبة، وتم استرجاع (85) استبانة. للمديريات و(80) صالحة لأغراض الدراسة. أظهرت النتائج الرئيسية للدراسة أن الضريبة المؤجلة في الجزائر لا تتوافق مع متطلبات معظم معايير المحاسبة الدولية حيث لم يكن هناك عرض للقوائم المالية، ولم يكن هناك اعتراف بالفروق الضريبية المؤقتة والفروق المؤقتة القابلة للخصم في الضريبة المؤجلة في الجزائر. The aim of this study is to measure the degree of compliance with deferred taxes in Algeria, to study and analyze the level of compliance with deferred tax through a questionnaire distributed to (97) certified accountants and accounting experts, and (85) questionnaires were retrieved for directorates and (80) were valid for the purposes of the study. The main results of the study showed that the deferred tax in Algeria does not comply with the requirements of most international accounting standards as there was no presentation of the financial statements, and there was no recognition of the temporary tax differences and the deductible temporary differences in the deferred tax in Algeria.
Keywords: الضرائب المؤجلة -- القوائم المالية -- المعايير المحاسبية -- المؤسسات الاقتصادية -- الجزائر